Kaedah perundangan, bidang kuasa dan tatacara mahkamah syariah - Ahmad Bustami, Tajul Aris (Dewan Bahasa dan Pustaka, 2005)
This book discusses the issues of jurisdiction of Syariah courts, legal maxims, Court procedure and ethics of Syariah lawyers and judges.